Promoting Students’ Conceptual Understanding through Directive Teacher Guidance and Non-directive Teaching Model in a Collaborative Problem Solving - Bunag, Ilene DS. (Future Science / FSH-PH Publications, 2024)
This study examined and aimed to promote students’ level of conceptual understanding in problem-solving through Directive Teacher Guidance (DTG) and the Non-directive Teaching Model (NDTM). The study employed sequential-explanatory mixed research using quasi-experimental switching replication treatment involving quantitative and qualitative data. Two groups of Grade 8 high school students were used as participants in the study. One group had 36 students, and the other had 38 students exposed to DTG and NDTM approaches. Quantitative data were obtained from the scores of students from the pretest, first posttest, and second posttest about the topics in Mathematics subject. Qualitative data were from the analysis of participants’ responses in problem-solving, focus group discussion, and classroom observation. The t-test for the dependent sample was utilized to determine the significant change in students’ level of conceptual understanding after the first and second implementation phases, while the t-test for the independent sample was used to find out the significant difference between the pretest and posttests between the two groups. Results showed that students’ conceptual understanding and problem-solving skills significantly improved after exposure to the two approaches. The two groups’ levels of conceptual understanding in switching replication treatment are found to have no significant difference. Moreover, participants preferred guided questions and guided directions and believed in the importance of attaining a conceptual understanding of the lesson. It is suggested to integrate DTG and NDTM as teaching strategies and conduct a study considering a longer span of implementation to determine the effectiveness of the two approaches.